Ethnobotanical Study of Underutilized Wild Edible Fruits and their Antibacterial Activity against Human Pathogens - Suresh Ch. Biswas; Pranab Dutta; Purnima Barua; Tarun Kr. Misra; Subrata Das (Journal of Pure and Applied Microbiology, 2021)
Nine underutilized wild edible fruits collected from four districts of Tripura, a North-Eastern state of India were studied for the antibacterial properties against five (5) human pathogens, Escherichia coli (Gram–Ve, ATCC-2522), Pseudomonas aeruginosa (Gram–Ve, ATCC-27853), Salmonella typhi (Gram –Ve, ATCC-14028), Staphylococcus aureus (Gram +Ve, ATCC-25923) and Klebsiella pneumonia (Gram–Ve, ATCC-700603) by disk diffusion method. Besides, the folk medicinal values and their ethnobotanical importance are also reported. Out of the nine (9) wild edible fruits, C. macroptera and S. dulcis showed the least antibacterial effect against all the bacterial pathogens under the present study. On the other hand, G. gummi-gutta and A. lacucha showed considerable antibacterial effects against all of the bacterial pathogens with the highest zone of inhibition against E. coli, followed by P. aeruginosa. Selective inhibitory effect of some of the wild edible fruits was also observed against the targeted pathogens. This study paves the way for using the underutilized wild fruits of the North-Eastern region of India as a potential source of antipathogenic activity of human pathogens. Further, a detailed study may help in identifying the bioactive compound of industrial importance.